The potential of environmental law and policy to influence the banking industry towards a green economy and ‘green lending’: a South African perspective - Rasool, Zainub (My University, 2018)
Through the implementation and strengthening of environmental laws and international standards, banks globally face direct and indirect liability, including reputational risks through the association of funding high risk activities having adverse environmental impacts. Environmental laws and international standards have created a specific focus on protecting the environment against environmental crimes and managing risks associated with activities that pose threats to the ecosystem. Although the alleged perpetrators of these environmental crimes are high risk industries which undertake operations that have a high negative environmental impact, banks need to contend with the possibility of attracting lender liability. Under South African legislation, lender liability is expressed through the duty of care principle which applies to all operations, businesses and individuals. Breach of environmental laws could lead to directors being prosecuted in the ordinary cause of law. There is also high focus being placed by the South African government to move towards a sustainable economy by addressing environmental concerns and reducing carbon emissions. Banks, who play a role in facilitating economic development through its lending operations can have a positive impact in promoting sustainable development through their processes. Based on the above, banks have proceeded to incorporate environmental considerations by adopting environmental management systems and sustainable solutions into their lending processes. This measure is adopted to minimise lender liability, facilitate sustainable development and contribute to the government’s goal to progress towards becoming a green economy.
Research report submitted in partial fulfilment of the requirements for the degree of Master of Laws (LLM) by Coursework and Research Report in the School of Law, Faculty of Commerce, Law and Management at the University of Witwatersrand, Johannesburg 2018
Keywords: Environmental law; Environmental protection